PENERAPAN METODE INQUIRY PADA MATERI HIMPUNAN - Istiani, Ana (JURNAL E-DUMATH, 2016)
This study aims to find the average of student learning achievement byimplementing inquiry and expository method on sets material. To determine thedifference between mathematics students learning achievement in the class thatused inquiry method and the class that used expository method are using t test ifthey are fulfill two assumptions they were normal and homogeneous distributions.Based on the data analysis concluded that any mathematics learning achievementaverage differences obtained by inquiry method on the sets material. It showedthat the students taught by inquiry method got better learning achievementaverage than the students taught by expository method.Keywords: inquiry method, expository method, students learning achievment